Combining Ability for Seed Yield and its Components in Brown Sarson in Arid Environment - Kumar, D (Annals of Arid Zone, 2016)
A diallel involving 10 inbreds of brown sarson, revealed the significance of non-additive gene effects in inheritance of plant height, main shoot length, number of siliquae on main shoot, number of primary branches/ plant, 1000-seed weight and seed yield/plant, whereas non-additive gene effects were important for number of secondary branches/plant. Two inbreds (IB 14 and I B 15) were best general combiners for seed yield, the former with maximum seed yield was also a good com’liner of siliquae on main shoot. IB 19 was characterized with maximum general combining ability cstimates and means for main shoot length, number of siliquae on main shoot and number of sccondary branches/plant. IB 10 x IB 19 followed by IB 10 x IB 15 and IB 15 x IB 19 were the best specific combiners for seed yield.